Therapeutic Effects of a TANK‐Binding Kinase 1 Inhibitor in Germinal Center–Driven Collagen‐Induced Arthritis. Issue 1 (26th November 2018) - Louis, Cynthia; Ngo, Devi; D'Silva, Damian B.; Hansen, Jacinta; Phillipson, Louisa; Jousset, Helene; Novello, Patrizia; Segal, David; Lawlor, Kate E.; Burns, Christopher J.; Wicks, Ian P.
Abstract : Objective: The production of class‐switched high‐affinity autoantibodies derived from organized germinal centers (GCs) is a hallmark of many autoimmune inflammatory diseases, including rheumatoid arthritis (RA). TANK‐binding kinase 1 (TBK‐1) is a serine/threonine kinase involved in the maturation of GC follicular helper T (Tfh) cells downstream of inducible costimulator signaling. We undertook this study to assess the therapeutic potential of TBK‐1 inhibition using the small‐molecule inhibitor WEHI‐112 in antibody‐dependent models of inflammatory arthritis. Methods: Using the models of collagen‐induced arthritis (CIA), antigen‐induced arthritis (AIA), and K/BxN serum‐transfer–induced arthritis (STIA), we determined the effectiveness of WEHI‐112 at inhibiting clinical and histologic features of arthritis in C57BL/6 and DBA/1 mice. We used immunohistochemistry to characterize GC populations during CIA development, and we used enzyme‐linked immunosorbent assays to determine levels of Ig autoantibodies in WEHI‐112–treated mice compared to vehicle‐treated mice. Results: WEHI‐112, a tool compound that is semiselective for TBK‐1 but that also has activity against IKKε and JAK2, abolished TBK‐1–dependent activation of interferon (IFN) regulatory factor 3 and inhibited type I IFN responses in vitro. In vivo, treatment with WEHI‐112 selectively abrogated clinical and histologic features of established, antibody‐dependent CIA, but had minimal effects on an antibody‐independent model of AIA or on K/BxN STIA. In keeping with these findings, WEHI‐112 reduced arthritogenic type II collagen–specific IgG1 and IgG2b antibody production. Furthermore, WEHI‐112 altered the GC Tfh cell phenotype and GC B cell function in CIA. Conclusion: We report that TBK‐1 inhibition using WEHI‐112 abrogated antibody‐dependent CIA. As WEHI‐112 failed to inhibit non–antibody‐driven joint inflammation, we conclude that the major effect of this compound was most likely the targeting of TBK‐1–mediated mechanisms in the GC reaction. This approach may have therapeutic potential in RA and in other GC‐associated autoantibody‐driven inflammatory diseases.